Performance Analysis of Working Time and Cost of Rigid Arteries Using Earned Value Analysis (EVA) Method: Case Study: of the construction project of the Becakayu toll access bridge on and off ramp Jatiwaringin - Famila Hasan; Fahmi (Journal of World Conference (JWC), 2021)
Time and cost control is a very important aspect of project management. Poor time control causes the project construction costs to differ from the planned costs. PT Waskita Beton Precast as the main contractor that carries out the construction of the on and off ramp Jatiwaringin arterial and bridge access projects has problems in controlling time and costs which can be seen in minus deviations in the work progress report. The research method with a quantitative descriptive approach is very supportive in making research by reviewing project performance with the earned value method. The data are processed and analyzed using Earned Value indicators so as to produce a performance index. The results of the study were seen from the deviation of the project progress of 31.57% so that a calculation analysis was carried out in terms of time. With the results obtained to complete the project it takes an additional 85 days from the end of the project contract. Based on the results of the cost calculation analysis. The total cost needed to complete all the work (EAC) is Rp. 48,402,991,553.33.